2021
DOI: 10.3389/fphar.2021.627123
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TLR4/MAPKs Pathway Contributes to the Protection of Salvianolic Acid A Against Lipotoxicity-Induced Myocardial Damage in Cardiomyocytes and Obese Mice

Abstract: The occurrence of lipotoxicity during obesity-associated cardiomyopathy is detrimental to health. Salvianolic acid A (SAA), a natural polyphenol extract of Salvia miltiorrhiza Bunge (Danshen in China), is known to be cardioprotective. However, its clinical benefits against obesity-associated cardiomyocyte injuries are unclear. This study aimed at evaluating the protective effects of SAA against lipotoxicity-induced myocardial injury and its underlying mechanisms in high fat diet (HFD)-fed mice and in palmitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Hepatic lipid accumulation induced by chronic alcohol intake, which in turn leads to lipotoxicity and further hepatocyte death, is a critical pathological mechanism in ALD. Previous studies including ours have indicated that TLR4/MAPKs pathway was mechanistically involved in alcohol- and lipotoxicity-induced hepatotoxicity [( Shen et al, 2018 ; Li et al, 2020 ; Yang et al, 2021 )]. Here, we evaluated the beneficial effect of abstinence on TLR4/MAPKs pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Hepatic lipid accumulation induced by chronic alcohol intake, which in turn leads to lipotoxicity and further hepatocyte death, is a critical pathological mechanism in ALD. Previous studies including ours have indicated that TLR4/MAPKs pathway was mechanistically involved in alcohol- and lipotoxicity-induced hepatotoxicity [( Shen et al, 2018 ; Li et al, 2020 ; Yang et al, 2021 )]. Here, we evaluated the beneficial effect of abstinence on TLR4/MAPKs pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Several literature reports suggest that PA induces myocardial damage that leads to cell death and cardiac dysfunction, thus providing an important method for inducing cardiac lipotoxicity in in vitro systems [ 52 , 53 , 54 ]. Accordingly, in this study, we first found that PA decreases cell viability and induces cell death in a dose-dependent manner (from 200 µM), indicating that an in vitro model of cytotoxicity induced by lipid overload has been successfully established.…”
Section: Discussionmentioning
confidence: 99%
“…Lipotoxicity originated from abnormal lipid metabolism played a seriously detrimental role in metabolic diseases, including fatty liver diseases, obesity, cardiovascular diseases, and diabetes. Several lines of evidence indicated that alleviating lipotoxicity was an effective strategy for preventing or improving multiple metabolic diseases [ 31 , 32 ]. However, no medication targeting lipotoxicity has been proved in clinics.…”
Section: Discussionmentioning
confidence: 99%